STUDY OF IR AND THERMAL ANALYSIS OF MODIFIED POLYVINYL CHLORIDE - Akhmedov Furkat Bakhtiyorovich; (PhD) Buvaraimov Ziyodullo Karimjon ugli; Nurkulov Fayzulla Nurmuminovich; Vokhidov Erkinjon Alievich (European Science Publishing, 2024)
Fire retardants based on polyphosphate ammonium-containing metal oligomers have been obtained. When comparing the IR spectroscopic analysis of the sample under study with analogues, it was found that the characteristic relationships are close to each other. Based on the results of DTA and TGA analysis, kinetic parameters were determined for various temperature ranges of the process. Its advantage is based on the experimental data obtained on the kinetics of processes in the temperature range from 100°C to 600°C; the properties of thermal-oxidative destruction of samples with 5-30% fire retardants have been studied.
Keywords: cable, fire resistance, polymer, coating, oligomer, fire retardant, monomer, polyvinyl chloride, composition, heat resistance, melamine, polyphosphate, grade, analysis, thermal, mass.